Sequence‐specific DNA binding by AT‐hook motifs in MeCP2. Issue 17 (9th August 2016) - Lyst, Matthew J.; Connelly, John; Merusi, Cara; Bird, Adrian
Abstract : MeCP2 is a chromatin‐associated protein that is mutated in Rett syndrome. Its methyl‐CpG‐binding domain interacts with DNA containing methylated cytosine, but other modes of recruitment to the genome have also been proposed. Here, we use in vitro and in vivo assays to investigate the DNA binding specificity of two AT‐hook motifs in MeCP2. One exhibits robust sequence‐specific DNA binding, whereas the other is a much weaker AT‐hook. Our data indicate that these motifs are secondary contributors to DNA binding by MeCP2, and this view is supported by the absence of disease‐causing missense mutations at these sites. Abstract :